2020
DOI: 10.1371/journal.pone.0236825
|View full text |Cite
|
Sign up to set email alerts
|

Fluid movements enhance creative fluency: A replication of Slepian and Ambady (2012)

Abstract: Bodily movements representing abstract concepts (e.g., fluidity) can affect divergent creative thinking. A recent study showed that participants who performed fluid arm movements by tracing curved line-drawings (the fluid condition) subsequently generated a larger number of more original alternative uses for newspapers than did those who traced angular linedrawings (the non-fluid condition). This suggests that fluid movements enhance fluency and originality in divergent creative thinking. To replicate these fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 49 publications
(68 reference statements)
1
11
1
Order By: Relevance
“…In summary, previous research has found small to moderate effects of fluid movement on creativity (Imaizumi et al, 2020;Slepian & Ambady, 2012), race conceptions, and affective concern (Slepian et al, 2014) and no effects of fluid movement on positive and negative emotions. Furthermore, all previous research has found no statistically significant differences in mood (i.e., how good or bad participants felt) between fluid and nonfluid conditions, and Ambady (2012, replicated in Imaizumi et al, 2020) found no statistically significant differences in self-reported difficulty of drawing the lines between fluid and nonfluid conditions.…”
Section: Aims Of the Present Study: Fluid Movement Replication And Sa...mentioning
confidence: 65%
“…In summary, previous research has found small to moderate effects of fluid movement on creativity (Imaizumi et al, 2020;Slepian & Ambady, 2012), race conceptions, and affective concern (Slepian et al, 2014) and no effects of fluid movement on positive and negative emotions. Furthermore, all previous research has found no statistically significant differences in mood (i.e., how good or bad participants felt) between fluid and nonfluid conditions, and Ambady (2012, replicated in Imaizumi et al, 2020) found no statistically significant differences in self-reported difficulty of drawing the lines between fluid and nonfluid conditions.…”
Section: Aims Of the Present Study: Fluid Movement Replication And Sa...mentioning
confidence: 65%
“…While handedness has been considered the primary testbed, experimenting with the BSH so far, researchers have also tried to verify the theory targeting other body parts or attributes. The targets include but are not limited to footedness [20], arm fluency [26], and pain perception [31]. In these studies, participants showed neurocognitive differences (or conversions) during the process with similar tendencies regarding the common body characteristics they share, which potentially validates the BSH theory.…”
Section: Other Body Attributes: Laterality Fluency Proprioceptionmentioning
confidence: 82%
“…Generally, the results showed that participants in portraying curved line-drawings (i.e., fluid condition) subsequently came up with more alternative uses of printed journals than did those who traced angular linedrawings, involving in non-fluid condition. A clear distinction to be made here is that the new experiment focuses on the divergence [26] rather than both divergence and originality [36]. The result suggests that fluid movement influences cognitive processing [36].…”
Section: Fluency and Creativitymentioning
confidence: 93%
See 2 more Smart Citations